A Case of COVID-19-Associated Pediatric Multisystem Inflammatory Syndrome in Shock Managed by Cytokine Filtration. (2nd February 2022) - Lalwani, Priyanka; Baskaran, Subashini; Uribe, Diego Arango; Ramaiah, Anil; Saqib, Aqdas; ElMesserey, Mohammed; Fathi, Emad M.; Tabata, Yuichi; Fink, Christoph; Pallavidino, Marco
Abstract : Multisystem inflammatory syndrome in children (MIS-C) after COVID-19 has been recognized as a complication arising due to cytokine storm. Several management strategies including intravenous immunoglobulin and immunomodulators have been reported. This case report highlights the use of a cytokine filter (oXiris®) in the management of MIS-C. Cytokine filters eliminate cytokines and reduce the demand for vasopressors in patients with other inflammatory conditions. A 7-year-old child with prolonged fever, vomiting, hypotension, elevated inflammatory mediators, and dilatation of coronary arteries on echocardiography was found to have positive SARS-CoV-2 IgG and PCR. He was diagnosed as MIS-C and was managed in the pediatric intensive care unit. He required ventilatory support, vasopressors, and continuous renal replacement therapy (CRRT) with a cytokine filter. He showed marked improvement within 24 hours of initiating CRRT. Cytokine filters may have a potential role in the management of severely ill children due to MIS-C. To our knowledge, this is the first report of successful use of the oXiris ® membrane in MIS-C. However, further case series and controlled trials are needed to establish its use in this condition.